Institutional Choice and Cooperation in Representative Democracies: An Experimental Approach - Fanny E. Schories (University of Hamburg, Institute of Law and Economics (ILE), 2017)
This paper examines whether an institution has a differing impact on cooperation if it is introduced by a representative of the affected parties rather than exogenously imposed. The experimental design is able to control for selection effects arising from the democratic policy choice. I find evidence of a large democracy premium in the sense that endogenously implemented institutions lead to more cooperation than iden- tical exogenous institutions. Especially the subjects who initially did not prefer the policy comply if it was brought about by an elected representative. The results have implications for the analysis of decision-making processes and policy recommendations in general.
Keywords: C9; D02; D72; 330; Laboratory Experiment; Representative Democracy; Collective Decision-Making; Social Dilemma; Legitimacy